Acute myocardial infarction complicating acute ulcerative colitis: A clinical conundrum - Krishna Vani Nemalidinne; Abinay Siva Kumar Reddy Vanteru; Amit Goel; Abhigan Babu Shrestha; Vikash Jaiswal (Clinical Case Reports, 2023)
Key Clinical Message Inflammatory bowel disease (IBD) is an immune‐mediated multisystem inflammatory disease that primarily affects the gastrointestinal tract, but it also has various extraintestinal manifestations like cardiovascular, dermatological, musculoskeletal, or hepatobiliary tract involvement. Herein, we describe a case of a 46‐year‐old female, who presented with acute coronary syndrome on the background of acute relapse of ulcerative colitis (UC), requiring a pragmatic clinical approach due to a labile balance between hemorrhagic and ischemic risk.